PEMIKIRAN PENDIDIKAN ISLAM DALAM PERSPEKTIF IMAM Al-ZARNUJI DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM PADA ERA SOCIETY 5.0 - Fadhilah Sukmawati Tanjung; Ganjar Eka Subakti (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2023)
Era Society 5.0 succeeded in coloring the world of Islamic education in Indonesia. The world of Islamic education is experiencing a digital transformation that brings real changes to people's paradigms and behavior. This study uses a type of qualitative research with the method of literature (library research). The results of the study found that the educational ideas formulated by al-Zarnuji were related to educational goals, curriculum, teachers, students, and learning methods. Al-Zarnuji's Islamic educational thinking is still relevant to be applied in the Society 5.0 era.